The constitutionalisation of administrative law in South Africa: an examination of the administrative justice clause in the interim constitution, case law pursuant thereto and proposals for the clause in the final constitution - Bozalek, Leonard John (Department of Public Law, 2024)
In February 1993 leading academic and practising administrative lawyers gathered in Cape Town for a three day workshop in order to conceive a vision of administrative law in the future South Africa. The portents and conditions for reform for this critical juncture of law and public power were the most propitious for nearly five decades. Three years had passed since the political logjam had been broken by the formal unbanning of the ANC and other proscribed movements and negotiations for a new democratic constitution were proceeding albeit intermittently by reason of sporadic politic crises. For those of the participants in the workshop who were close to constitutional negotiations it must have been clear that the smokefilled rooms of Kempton Park would eventually produce a Bill of Rights with an administrative justice clause and thus an opportunity to rescue South African administrative law from its increasingly justified description as a "dismal science". The workshop appears to have been an outstanding success, at least seen from the perspective of an outside observer and taking into account the plethora of legal conferences which seem an inevitable by-product of times of constitutional ferment. Apart from the publication of a widely read book containing many of the challenging and thought provoking papers read at the workshop, the Workshop's overriding contribution may well have been the intensive sharing of ideas and discussions directed towards seeking to expand the horizons of South African administrative law. This harnessing of disparate energies led to the historic Breakwater Declaration.